Deciphering the Crosstalk Between Myeloid-Derived Suppressor Cells and Regulatory T Cells in Pancreatic Ductal Adenocarcinoma - Siret, Carole; Collignon, Aurélie; Silvy, Françoise; Robert, Stéphane; Cheyrol, Thierry; André, Perrine; Rigot, Véronique; Iovanna, Juan; van de Pavert, Serge; Lombardo, Dominique; Mas, Eric; Martirosyan, Anna (Frontiers in Immunology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is a fatal disease with rising incidence and a remarkable resistance to current therapies. The reasons for this therapeutic failure include the tumor’s extensive infiltration by immunosuppressive cells such as myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs). By using light sheet fluorescent microscopy, we identified here direct interactions between these major immunoregulatory cells in PDAC. The in vivo depletion of MDSCs led to a significant reduction in Tregs in the pancreatic tumors. Through videomicroscopy and ex vivo functional assays we have shown that (i) MDSCs are able to induce Treg cells in a cell-cell dependent manner; (ii) Treg cells affect the survival and/or the proliferation of MDSCs. Furthermore, we have observed contacts between MDSCs and Treg cells at different stages of human cancer. Overall our findings suggest that interactions between MDSCs and Treg cells contribute to PDAC immunosuppressive environment.